Advancements and strategies of genetic improvement in cassava (Manihot esculenta Crantz): from conventional to genomic approaches - Xiao, L.; Cheng, D.; Ou, W.; Chen, X.; Rabbi, I.Y.; Wang, W.; Li, K.; Yan, H. (Oxford University Press, 2025)
Cassava (Manihot esculenta Crantz) is a staple food of 800 million people in the tropical and subtropical regions of the world. Its industrial utilization for bioethanol, animal feed, and starch are still continuously expanding. It was not until the 1970s that significant scientific efforts were undertaken to improve cassava, despite its considerable economic and social significance. Shortening the breeding cycle and improving the breeding efficiency are always the focus of the cassava breeding study. In this review, we provide a global perspective on the current status of cassava germplasm resources and explore the diverse applications of cassava breeding methods from hybridization, polyploidy, and inbreeding to genomic selection and gene editing. Additionally, we overview at least six nearly complete cassava genome sequences established based on modern genomic techniques. These achievements have substantially supported the advancing of gene discovery and breeding of new cassava varieties. Furthermore, we provide a summary of the advancements in cassava’s functional genomics, concentrating on important traits such as starch quality and content, dry matter content, tolerance to postharvest physiological deterioration, nutritional quality, and stress resistance. We also provide a comprehensive summary of the milestone events and key advancements in cassava genetic improvement over the past 50 years. Finally, we put forward the perspective of developing genomic selection breeding model and super-hybrids of cassava through building inbreeding population and emphasize the generation of triploid cassavas, as well as using gene editing technology allowing cassava to be a tropical model plant to serve for basic biological research and molecular breeding.